Making tough choices: A policy capturing approach to evaluating the tradeoffs in sustainable supplier development initiatives. Issue 5 (December 2019) - Rogers, Zachary S.; Carter, Craig R.; Kwan, Virginia
Abstract: This research explores the tradeoffs that decision makers are willing to make when implementing development initiatives to improve supplier sustainability performance. We employ a policy capturing methodology in which respondents are forced to choose between multiple potential sustainable supplier development initiatives. Data were collected from traditional and executive MBA students. The results suggest that when confronted with tradeoffs, decision makers value improvements in supplier cost savings and injury reduction equally, which was somewhat unexpected. Further, both improvements in supplier cost savings and injury reduction were valued over supplier emissions performance. Because we measure individual tradeoff preferences, multi-level regression analysis was used to better understand the impact of respondent value structure regarding sustainably developing suppliers. Our findings suggest a hierarchy of tradeoff preferences for decision makers as they pertain to sustainable supplier development. As the pressure to ensure supply chain sustainability increases, more firms will engage in sustainable supplier development. The outcomes of the choices they make when choosing between initiatives, and how managers make these choices, will be of increasing interest in both industry and academia. This research answers previous calls for further examination of decision maker tradeoff preferences in sustainable supply chain development. Highlights: Analysis suggests that sustainable supplier development tradeoff preferences exist. Decision makers value improvements in supplier cost savings and injury reduction equally – both are valued over supplier emissions reductions. Moderate levels of supplier sustainability improvement across multiple metrics are preferred over significant improvement in a single metric. Key personality factors impact tradeoff preferences for supplier savings and emissions improvement, but not for injury reduction.